Correctional Institution’s Construction In The Death-Convicted Supervision - Azzahra Rizki Ananda (Pancasila and Law Review, 2021)
The death row inmate becomes one of the members of the Correctional Institution or Lembaga Pemasyarakatan (Lapas) when the convict is waiting for the execution time or if the convict is still making a legal effort. This raises problems from the aspect of the rules, which form the basis of prisons' authority in the guidance of death row inmates because the provisions on the development of capital punishment do not have specific regulations. The problem in this research is the urgency of guiding death convicts in prison; how it is implemented, and is there any difference in the guidance for death row inmates in prison; construction or ideal model of guidance for death row inmates in prison; as a result of the law, guidance on death row inmates is carried out in Lapas. This study uses a normative and empirical juridical approach with data collection methods using literature and field studies. The study results show that the prison's guidance is essential considering that the person concerned will be executed, so assistance and supervision are needed to prevent unwanted things, for example, committing a crime, suicide, or experiencing depression. Death row convicts follow other prisoners' proper guidance, provide useful activities to death convicts, and provide the death convicts with the rights. The superior construction for the development of capital punishment is contained in the Criminal Code Draft or Rancangan Kitab Undang-Undang Hukum Pidana (RKUHP), which makes capital punishment an alternative punishment, provides a probation period of 10 years for the death row inmates, the superior construction of both the place and the material for its guidance must be distinguished from those sentenced to other types of crimes. As a result of the law, there is no certainty of guidance for death row inmates in prison because there are no specific regulations regarding death penalty services.